Analysis Of Financial Improvement Of Coastal Communities Through The Business Of Processing Rebon Shrimp Into Terasi - Nasution, Zena Aini; Harahap, Isnaini; Marliyah, Marliyah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines how processing rebon shrimp into shrimp paste can enhance the financial stability of coastal communities in Kualuh Leidong District, North Sumatra. The motivation stems from the low economic conditions of local fishermen and their vulnerability to catch fluctuations, despite the region’s potential for high-value marine product processing. Using a descriptive qualitative approach, data was gathered through interviews, observations, and documentation at several shrimp paste producers in Tanjung Leidong Village. Findings indicate that turning rebon shrimp into paste significantly boosts household income, helps meet basic needs, enables savings or business investment, broadens market reach, and encourages community participation in MSME activities. Field data shows income improvements; for instance, Meichen's earnings increased from IDR 36-84 million in 2023 to IDR 60-120 million in 2024. Furthermore, Tanjung Leidong's shrimp paste products are well known and marketed at the North Sumatra Fair (PRSU). Nonetheless, challenges persist, including limited capital, basic technology, and inadequate financial record-keeping systems. In conclusion, shrimp paste processing in Kualuh Leidong has strong potential to foster sustainable local economic growth, especially if supported by government and stakeholders through entrepreneurship training, capital access, and digital marketing development.